1999
DOI: 10.1152/ajpendo.1999.277.6.e1013
|View full text |Cite
|
Sign up to set email alerts
|

High nocturnal body temperatures and disturbed sleep in women with primary dysmenorrhea

Abstract: Primary dysmenorrhea is characterized by painful uterine cramps, near and during menstruation, that have an impact on personal life and productivity. The effect on sleep of this recurring pain has not been established. We compared sleep, nocturnal body temperatures, and hormone profiles during the menstrual cycle of 10 young women who suffered from primary dysmenorrhea, without any menstrual-associated mood disturbances, and 8 women who had normal menstrual cycles. Dysmenorrheic pain significantly decreased su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
92
2
5

Year Published

2001
2001
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(110 citation statements)
references
References 25 publications
7
92
2
5
Order By: Relevance
“…The mean menstrual phase cortisol and prolactin levels in this study were above normal range for premenopausal women. This result is contrary to the study of Baker et al, (1999), who reported that only in the luteal phase does the mean prolactin secretion for dysmenorrhoeic subjects rise above the normal range. Elevated prolactin and cortisol recorded in this study may be due to the discomfort of venepuncture pre and post TENS application apart from the menstrual pain, since the two hormones are stress related (Stromberg et al, 1981;Kaplan et al, 1991) CONCLUSION This study concluded that high frequency TENS significantly reduced the pain levels in dysmenorrhoeic women without significantly affecting serum levels of cortisol and prolactin level.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The mean menstrual phase cortisol and prolactin levels in this study were above normal range for premenopausal women. This result is contrary to the study of Baker et al, (1999), who reported that only in the luteal phase does the mean prolactin secretion for dysmenorrhoeic subjects rise above the normal range. Elevated prolactin and cortisol recorded in this study may be due to the discomfort of venepuncture pre and post TENS application apart from the menstrual pain, since the two hormones are stress related (Stromberg et al, 1981;Kaplan et al, 1991) CONCLUSION This study concluded that high frequency TENS significantly reduced the pain levels in dysmenorrhoeic women without significantly affecting serum levels of cortisol and prolactin level.…”
Section: Discussioncontrasting
confidence: 99%
“…Also hormonal imbalance has been linked as contributing factors to the pain experienced during menstruation (Baker et al, 1999). Considering the recent popularity of TENS in managing PD because of its efficacy and minimal side-effect and the hormonal imbalance reported to be a contributing factor to menstrual pain.…”
Section: Introductionmentioning
confidence: 99%
“…Spindle frequency is also increased during the luteal phase but an association with progesterone has not been found [10]. Although stage REM sleep is reduced during the luteal phase [9,10,85,94,97], a direct association between REM sleep amounts and progesterone is less clear [10,96].…”
Section: Reproductive Hormonal Milieu Influences Sleepmentioning
confidence: 96%
“…They were asked to give a written comment on any special or distressing event that had occurred during the day. This method of mood assessment has been used previously in premenopausal women (Baker et al 1999). Certain individuals are susceptible to mood changes that are dependent on variations in the concentration of ovarian hormones (Reilly 2000).…”
Section: Performance Trialsmentioning
confidence: 99%